Peningkatan Kemampuan Berbicara Bahasa Inggris Siswa Madrasyah Ibtidaiyah Melalui Teknik Pembelajaran Picture And Picture - Nurul Muttaqien; Awiria (Madako Elementary School, 2022)
The difficulty of elementary school students in mastering speaking  English ability is caused by several things, including lack of vocabulary, pronunciation, and lack of mastery of teacher learning techniques in teaching. This study aims to find out how picture and picture learning techniques can improve students' speaking abilities. This research method uses a classroom action research method with two cycles. The results of this study indicate an increase in speaking of students in each cycle, first  cycle with a percentage of 62,5% and 78,75% in scond cycles’.